2008
DOI: 10.11646/zootaxa.1682.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Description of a new genus and two new species of labeonine fishes from South China (Teleostei: Cyprinidae)

Abstract: A new genus and two new species are described from the Pearl River drainage in Guangxi Province, South China. Hongshuia, new genus, can be distinguished from all other Asian genera of the Labeonini by having a lower lip with its median lobe modified into a round, fleshy plate peripherally greatly protruded so as to form a ring-like fold that is posteromedially continuous with the mental region, and centrally sunken so as to form a round, flat, fleshy pad. This genus is distinct from all other Asian labeonine g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The new specimens had distinct phenotypes and could not be assigned confidently to any genus. These observations combined with the morphological and molecular analyses of previous studies (Zhang et al 2000;Zhang & Chen 2004;Zhang et al 2008;Zhang & Zhou 2012), convince us that a new genus is warranted for these specimens, which is described herein.…”
Section: Introductionsupporting
confidence: 74%
“…The new specimens had distinct phenotypes and could not be assigned confidently to any genus. These observations combined with the morphological and molecular analyses of previous studies (Zhang et al 2000;Zhang & Chen 2004;Zhang et al 2008;Zhang & Zhou 2012), convince us that a new genus is warranted for these specimens, which is described herein.…”
Section: Introductionsupporting
confidence: 74%
“…Therefore, it is necessary to know whether other cyprinine fishes traditionally not considered as barbins also possess fewer than three rows of pharyngeal teeth. Following further literature review, we identified the following genera with fewer than three rows of teeth: Carassius (1 row; Luo & Yue 2000), Carassioides (2 rows; Luo & Yue 2000), Discocheilus (2 rows; Zhang et al 2000), Discogobio (2 rows; Zhang et al 2000), Hongshuia (2 rows; Zhang et al 2008 Chen & Cao 2000). Among all the genera listed above, nine genera Probarbus, Catlocarpio, Scaphognathops, Carassius, Carassioides, Chuanchia, Gymnocypris, Oxygymnocypris and Platypharodon were sampled in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Since Sinocrossocheilus was erected by Wu (1977), 10 species have been consecutively described: S. guizhouensis , S. tridentis , S. microstomatus , S. labiatus , S. longibullus , S. nigrovittatus , S. papillolabrus , S. bamaensis , S. liuchengensis and S. megalophthalmus (Cui & Chu 1986; Wang & Chen 1989; Su et al, 2003; Chen et al 2006). Hongshuia was recently erected by Zhang (2008). Two species previously assigned to Sinocrossocheilus ( S. microstomatus and S. megalophthalmus ) were later placed in Hongshuia by Yuan et al .…”
Section: Discussionmentioning
confidence: 99%
“…(2000) on basis of morphology, several new genera (e.g. Hongshuia , Qianlabeo and Stenorhinchus ) were erected (Zhang & Chen 2004; Zhang & Fang 2005; Li et al, 2006; Huang 2007; Zhang et al, 2008), and the generic assignment of some species were rearranged (Yuan et al 2008). The description of these new genera and re‐division of species were mainly based on the oromandibular morphology, without any input from molecule‐based phylogenetic evidence.…”
Section: Introductionmentioning
confidence: 99%